2014
DOI: 10.1002/2013ja019398
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of wavelet technique to highlight the observed geomagnetic perturbations linked to the Chilean tsunami (2010)

Abstract: The vertical component (Z) of the geomagnetic field observed by ground‐based observatories of the International Real‐Time Magnetic Observatory Network has been used to analyze the induced magnetic fields produced by the movement of a tsunami, electrically conducting sea water through the geomagnetic field. We focus on the survey of minutely sampled geomagnetic variations induced by the tsunami of 27 February 2010 at Easter Island (IPM) and Papeete (PPT) observatories. In order to detect the tsunami disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…Perturbations in the geomagnetic field induced by the tsunami have been observed by several authors [ Balasis and Mandea , ; Manoj et al , ; Toh et al , ; Utada et al , ; Klausner et al , ] and modeled [ Tyler , ; Kherani et al , ; Minami and Toh , ; Zhang et al , ; Kherani et al , ] in the previous literature.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Perturbations in the geomagnetic field induced by the tsunami have been observed by several authors [ Balasis and Mandea , ; Manoj et al , ; Toh et al , ; Utada et al , ; Klausner et al , ] and modeled [ Tyler , ; Kherani et al , ; Minami and Toh , ; Zhang et al , ; Kherani et al , ] in the previous literature.…”
Section: Introductionmentioning
confidence: 90%
“…In the present study, we focus on identifying both near‐ and far‐field tsunamigenic disturbances arising from ionospheric currents. Previous work done by Klausner et al [] has identified the tsunamigenic disturbances in the vertical component of the geomagnetic field. Likewise, presenting all three components of magnetic disturbances during the Japanese tsunami (2011), Kherani et al [] have found the tsunamigenic disturbances mainly in Z component.…”
Section: Introductionmentioning
confidence: 99%
“…The high computational cost involving procedures in the continuous wavelet transform [ Daubechies , ; Mendes et al ., ] could be solved using an adequate discrete wavelet transform. Wavelet transform takes only discrete wavelets [ Mendes et al ., ; Ojeda González et al , ; Klausner et al ., ]. Depending on discretization outline used there can be redundant representations that can be avoided choosing orthogonal wave functions, the DWT as wavelet coefficients written as djk = 2 − j /2 ∫ f ( t ) Ψ j − k dt , where Ψ j k ( t ) = 2 − j /2 Ψ (2 − j ( t − k )), in which j is the discrete value of scale and k is the localization.…”
Section: Methodologiesmentioning
confidence: 99%
“…Besides this, it also detects the singularities presence in the signals (Domingues et al, 2005;Mendes et al, 2005). The larger and smaller values of amplitude of wavelet coefficients direct the energy deposited in the ring current and also show their localized positions (Klausner et al, 2014). The highest and lowest values of square wavelet coefficient during acute active stage and quiet condition are their indicators.…”
Section: Discrete Wavelet Transform (Dwt)mentioning
confidence: 99%